Performance evaluation of multiple tuned inerter‐based dampers for seismic induced structural vibration control. Issue 1 (29th September 2021) - Chen, Huating; Bi, Kaiming; Liu, Yanhui; Tan, Ping
Summary: Recently, many kinds of tuned inerter‐based dampers (TIDs) have been developed due to the mass amplification property of inerters. These devices normally present better control performances compared with the conventional tuned mass damper (TMD). For a single TID installed on a main structure, similar to the single TMD system, its control behavior is sensitive to the changes in the parameters of the main structure, and mistuning may occur. The control effectiveness can then be significantly reduced. To solve this problem, multiple TMD (MTMD) system has been developed. Similar to the MTMD system, this paper proposes a multiple TID (MTID) system for seismic induced vibration control of engineering structures. Four types of MTIDs, depending on the connection configuration of the dashpot, spring, and inerter elements, are considered. The optimum design parameters of the MTID systems are firstly obtained with the assumption of a white‐noise excitation. The distribution of the optimum design parameters, the control performance, the stroke of each TID, and the robustness of the control system are then systematically investigated. Moreover, the control effectiveness of the optimized MTIDs is also examined under natural ground motions, and comparisons among the four types of MTIDs as well as the conventional MTMD are conducted. The analytical results show that among these control schemes, two types of MTIDs, that is, (a) the parallel connection of the spring and dashpot with the series connection of the inerter and (b) the parallel connection of the inerter and dashpot with the series connection of the spring, have pronounced control performances to suppress the displacement and absolute acceleration responses of the main structure.